Tinjauan Yuridis atas Pencabutan Status Tersangka terhadap Tersangka yang Melakukan Provokasi untuk Melakukan Kekerasan Hingga Menyebabkan Kematian - Cumbhadrika, Chitto; Pradhana, Heykal (HUMANIORUM, 2024)
The determination of suspect status in Indonesian criminal procedural law is a crucial step based on sufficient and legitimate preliminary evidence. According to the Criminal Procedure Code (KUHAP) Article 1 Paragraph (14), an individual may be designated as a suspect if there is adequate preliminary evidence pointing to a criminal act. However, this suspect status does not always result in a continuation of the investigation, as it can be revoked if insufficient evidence is found or if the alleged act is not considered a criminal offense. This article discusses the process of establishing and revoking suspect status, with an examination of a particular case involving WJP, a suspect whose status was later revoked. The analysis focuses on the available evidence and expert testimony, particularly from a language expert, who interpreted WJP's statements to assess whether they could potentially be considered a provocation for assault. By emphasizing the principle of objectivity in law enforcement, this paper also examines the importance of legitimate evidence and accurate evaluation in determining the continuation or cessation of an investigation. The study aims to provide a deeper understanding of the legal process and highlights the significance of transparency, accountability, and objectivity in the investigative and prosecutorial stages to ensure justice within Indonesia’s criminal justice system.